The inculcation of higher order thinking skills in history subject through the application of multiple intelligence theory - Ramasamy, Sivapakkiam; Abd. Rahman, Fadzilah; Abdul Manaf, Umi Kalthom; Said, Rozita @ Radhiah (Human Resource Management Academic Research Society, 2018)
In accordance to the needs and current educational policy, higher-order thinking skills (HOTS) have become the focus in daily teaching and learning processes. History is regarded as a must-pass subject for the Malaysia Certificate of Education (SPM) since the year 2013. Therefore, the Ministry of Education of Malaysia (MoE) highly recommends History teachers to apply various teaching strategies that could attract students’ interest towards learning the subject. One of which is the Multiple Intelligence Theory, proposed by Howard Gardner in 1983. A qualitative study was carried out to identify the type of multiple intelligence applied and the teaching approaches that complement the identified intelligence during the inculcation of HOTS in History subject. The samples involved were three Excellent History Teachers. The data were collected through the process of triangulation, of which teaching and learning process observation, interview, and document analysis. The data were then analysed and triangulated using the ATLAS.ti 7.0 software. The findings showed that all informants applied the verbal-linguistic, interpersonal, and visual-spatial intelligence dominantly during the process of inculcating HOTS in History subject. Excellent History Teachers were also found complementing other teaching approaches such as discussion, questioning, and graphical presentation with the appropriate multiple intelligence in inculcating HOTS among students.